Physicochemical properties and antibiofilm activity of mineral trioxide aggregate associated with farnesol - Castro-Núñez, Gabriela Mariana (2024)
This study assessed the physicochemical and antibiofilm properties of white mineral trioxide aggregate (MTA) associated with 1 or 2% of farnesol. Setting time was evaluated based on ISO 6876/2012. Radiopacity was evaluated by radiographic analysis. pH was assessed after time intervals of 1, 3, 7, 14, 21, and 28 days. Solubility (% mass loss) and volumetric change (by micro-CT) of the cements were evaluated after immersion in distilled water. The presence of voids inside the materials was assessed by using micro-CT. Antibiofilm activity against Enterococcus faecalis was evaluated by crystal violet assay and the modified direct contact test performed with biofilm previously formed on bovine root dentin for 14 days. Data were submitted to ANOVA/Tukey tests with 5% significance level. The incorporation of farnesol into MTA increased its setting time, but decreased its solubility at 30 days and its volumetric loss in all periods (p < 0.05). Radiopacity and solubility after 7 days were similar among the materials (p > 0.05). The association of farnesol showed the highest pH value after 1 and 3 days (p < 0.05). The association of farnesol with MTA promoted a decrease in the presence of voids, and increased the antimicrobial activity on biofilm biomass of E. faecalis (p < 0.05). In conclusion, the addition of farnesol can be suggested to improve the antimicrobial properties and the consistency of MTA.